Three-dimensional surface topography of graphene by divergent beam electron diffraction - Tatiana Latychevskaia (Nature Portfolio, 2017)
Graphene, and other 2D materials, do not exist as strictly planar sheets but instead have topographic ripples on the sub-nanometre scale. Here, Latychevskaiaet al. present a method to non-invasively image ripples in 2D materials with a single-shot, wide-area, electron diffraction measurement.